Analogy and the danger of over-simplifying the past. (19th July 2016) - Denbow, James
Abstract : This is an excellent and tightly written argument against the indiscriminate and essentialist extension of invented anthropological typologies, such as 'the San', back into the Pleistocene. While analogical arguments that relate similarities in excavated tools, poisons and so on to the repertoire of items used by extant peoples in order to interpret their function is a common approach in archaeology, as the authors rightly point out, the extension of these analogies to include particular cultural and linguistic forms is 'a theoretically flawed exercise'.